Dispositivo de violência letal práticas e regulação da letalidade pela polícia e pelo Primeiro Comando da Capital (PCC) em São Paulo - Romero, Gabriel De Sousa [UNIFESP] (2020)
The democratic transition at the end of the 80’s and the proeminent urgency of the “Primeiro Comando da Capital” (PCC), created inside of the paulista penitentiary system in the early 90’s, demanded a reformulation of the sociological set of questions about public security and violence. In this sense, the purpose of the present dissertation is to highlight the practice of the lethal violence by the PCC and the police, analysing their characteristics, particularities and the interconnection points between the legal and illegal practices that protagonize their representants in the lethality determination in São Paulo. The research seeks to qualify the organization of the lethal actions of the PCC’s “brothers” under the sight of their position in the resolution of interpersonal conflicts in the prisons and some territorialized areas in São Paulo. The organization is identified as having reconfigured the “world of crime” putting together the operation of illegal practices (drug traffic, theft e etc.) in favour of personal progress idea and the collective fight against the system. Paradoxically, the combat of the “organized crime” it’s one of the more recurrent justifications for a more repressive speech (violent), that reaffirm the regularity of lethal actions by the agents of the forces of state order. The problems related to the police lethality shows that the conditions and the consequences of the legal monopoly exercise of the use of the force in Brazil in general, are decisive to the discussions about the occurrence and control of violent lethal crimes. Starting from secondary sources and Michel Foucault’s theories about the triad “power-knowledge-subject”, this research seeks to contribute to the academic debate and to the public debate about the excruciating and nagging violent lethality problem in Brazil. Fulfilling answer to the matter of the lethal violence production device duration and the organization of that lethality by PCC means and the police, in a social dynamic marked by a highlighted criminal moral organization and by police practices that reproduce each more a violent perspective of the crime combat.